2016
DOI: 10.1186/s40410-016-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation actions for integrated climate risk management into urban planning: a new framework from urban typologies to build resilience capacity in Santos (SP)

Abstract: Introduction: Many coastal cities have recently recognized the need to adapt to climate change, given the increased frequency of disasters cause by severe weather events. Based on concepts about vulnerability and resilience, we identify the limitations and opportunities of synergy between different areas of municipal action.Case description: This paper explores the emerging linkages between city planning process and environmental disasters prevention in Santos (Brazil). To help visualize this process, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Therefore, the amount and distribution of beached debris on the beach vary in a way that is not fully known, and this takes place predominantly when heavy rainfall that is associated with flooding in urban areas changes the estuary's internal hydraulic flow. Storms and hangovers that produce strong tidal currents, waves and winds also bring debris from other areas to Santos beaches (Young 2016). CCA showed that the estuary's mouth was the stretch where the highest concentration of heavy and less buoyant debris occurred, such as mollusk shells, ropes, glass, stones and metals.…”
Section: Heavy Debrismentioning
confidence: 99%
“…Therefore, the amount and distribution of beached debris on the beach vary in a way that is not fully known, and this takes place predominantly when heavy rainfall that is associated with flooding in urban areas changes the estuary's internal hydraulic flow. Storms and hangovers that produce strong tidal currents, waves and winds also bring debris from other areas to Santos beaches (Young 2016). CCA showed that the estuary's mouth was the stretch where the highest concentration of heavy and less buoyant debris occurred, such as mollusk shells, ropes, glass, stones and metals.…”
Section: Heavy Debrismentioning
confidence: 99%
“…3, 4, 5) and some of them have already been selected by the Local Plan for future transformations. They make up the sample of the territory transformation being studied, considering infill as a transformation intervention able to reduce soil consumption (Young 2016), in accordance with the Local Plan indications.…”
Section: Fig 2 Modelbuilder For Classifying Lidar Data In Las Datasetmentioning
confidence: 99%
“…Discussed by Young (2016) in the study in Santos, Mexico, the present study also assumes that these planning documents are result of the region's cognition of planning for the present and future taking into account all the aspects; strengths, weaknesses; needs and requirements of MMR where climate change learning and reasoning plays an important part, and therefore this RP reflects the strength of the mitigation and adaptation strategies to be implemented.…”
Section: Regional Plan 1996-2011mentioning
confidence: 99%